Hadis-Hadis tentang Peserta Didik - Siahaan, Amiruddin; Hidayah, Nur (Nadwa, 2014)
This article explains that learners should earnestly seek knowledge or perse-verance in either theology or science. In addition, if the students have gained knowledge, then that knowledge should be employed well and teaches it to others. Meanwhile, science is only acquired by learning. Learner is one com-ponent input in the education system, which is further processed in the educa-tional process, so that it becomes a qualified human in accordance with the national education goals. A student has a very important role in education. It was described in many traditions (hadis) associated with virtue, character, and requirements of the learners. These hadis will be explained later in this article and will be takhrij to determine the position of these traditions.